2020
DOI: 10.1080/14756366.2020.1715388
|View full text |Cite
|
Sign up to set email alerts
|

A class of carbonic anhydrase IX/XII – selective carboxylate inhibitors

Abstract: A small series of 2,4-dioxothiazolidinyl acetic acids was prepared from thiourea, chloroacetic acid, aromatic aldehydes, and ethyl-2-bromoacetate. They were assayed for the inhibition of four physiologically relevant carbonic anhydrase (CA, EC 4.2.1.1) isoforms of human (h) origin, the cytosolic hCA I and II, and the transmembrane hCA IX and XII, involved among others in tumorigenesis (hCA IX and XII) and glaucoma (hCA II and XII). The two cytosolic isoforms were not inhibited by these carboxylates, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…The inhibition of the AChE enzyme results in the blockage of ACh hydrolysis. All compounds were again synthesised by one-pot three component cyclocondensation reaction from the amine, a substituted benzaldehyde and a mercaptocarboxylic acid [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the AChE enzyme results in the blockage of ACh hydrolysis. All compounds were again synthesised by one-pot three component cyclocondensation reaction from the amine, a substituted benzaldehyde and a mercaptocarboxylic acid [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…[61] Then, refluxing the pseudothiohydantoin 10 with hydrochloric acid for 8 : 10 hr gives TZD (Scheme 13). [62,63] Many modifications were made to this method, including one-pot synthesis or using microwave radiation for the acceleration of the reaction time. [64,65] Optimization of reaction conditions has shown that it can be carried out in water or hydrochloric acid.…”
Section: From Thioureamentioning
confidence: 99%
“…[23] Alhameed et al reported 2,4-dioxothiazolidine acid derivatives (VIII) as selective carbonic anhydrase IX and XII inhibitors. [24] In the current work, we designed and synthesized four new, differently substituted Rhodanine derivatives and evaluated for their inhibitory activity against carbonic anhydrase I, II, IX, and XII isoforms. Interestingly, few tested compounds exhibited good to moderate inhibition against the cytosolic isoform hCA II and tumor-associated hCA IX.…”
Section: Rationalementioning
confidence: 99%